Outcome and attributable cost associated with bacterial resistant infections in a tertiary care hospital - Prashant Chandra, Stanly Elstin Anburaj, Kunikatta Vijayanarayana, Kalwaje Eshwara Vandana,, Chiranjay Mukhopadhyay,,, Udupi Dinesh Acharya, Mallayasamy Surulivelrajan,, Vilakkathala Rajesh, (Journal of Applied Pharmaceutical Science, 2023)
Globally, the public and economic well-being is seriously threatened by antimicrobial resistance (AMR). The study aimed to identify the outcomes and attributable cost of treatment in patients with resistant bacterial infections. A prospective observational study was carried out for 30 months in adult patients admitted to a tertiary care teaching hospital. Patients diagnosed with clinical infection were included. Antimicrobial susceptibility testing was performed and interpreted according to the Clinical and Laboratory Standard Institute guidelines. Direct costs were collected and reported as median and range. Multiple linear regression was performed to identify the association between the attributes and costs. A high prevalence of management of multidrug-resistant (MDR) and extensive/pan-drug-resistant Gram-negative and MDR Gram-positive isolates was identified. Gram-negative isolates were highly resistant to β-lactam/β-lactamase inhibitors (62%–90%), fluoroquinolones (72%–91%), and carbapenems (58%–94%). Overall mortality was 17%. Median antibiotic costs were higher for patients with polymicrobial infections [$316 ($89–$1,248)], followed by intensive care unit patients [$184 ($70–$417)]. The overall cost for hospital-acquired infections [$2,431 ($1,223–$5,191)] was 2.5 times the cost of community-acquired infections [$902 (540–1,520)]. Hospital-acquired infections, mortality, length of stay, and resistant strains of Escherichia coli, Klebsiella spp., and Acinetobacter spp. were significantly associated with higher treatment costs (p ≤ 0.05). Lowering AMR with the judicious use of antibiotics and effectively strengthening the hospital’s infection control program can reduce the financial burden.
Keywords: Antimicrobial resistance profile, community-acquired infections, hospital-acquired infections